Flow current field observation with underwater moving acoustic tomography - Xu, Shijie; Feng, Rendong; Xu, Pan; Hu, Zhengliang; Huang, Haocai; Li, Guangming (Frontiers in Marine Science, 2023)
Underwater environment observation with underwater acoustic tomography has been considerably developed in recent years. Moving sound transmission can obtain the observation of entire spatial area with sound station moving. Various internal structures, unique surface and submarine boundaries and changing environment constitutes a complex acoustic propagation channel. This paper focus on the inversion method and signal resampling for sound moving transmission. Also, the current field in three-dimensional (3D) scale is also studied. A five-station sound transmission experiment with four moored station and one moving station that conducted in range of 500m×500m at Huangcai reservoir, Changsha, China is presented. Signal resampling is performed to get correlation of received acoustic data. The vertical layer-averaged flow current results between moving station and moored station are inversed with 2D grid method. 3D flow current field result is composed by grid-averaged inversion current of vertical profile via moving station at different moment. The received results of reciprocal signal transmission between two moored stations and one moving station were used for layer-averaged current variations at vertical scale and grid-averaged current. The feasibility of the method in underwater moving acoustic tomography research is proved and its applicability is discussed.